Black Seed Oil, Bentonite Clay, and Probiotics: A Comprehensive Holistic Cure for Clostridium difficile Infection in a 2-Year-Old Female Child - Emily Littman; Nicole Winningham; Tana B. Carson; Ivette M. Hidalgo (Case Reports in Infectious Diseases)
There has been a rise in antibiotic resistance in secondary conditions such as Clostridium difficile (C. difficile) due to overuse of antibiotics. Oral antibiotics are used to treat C. difficile, which further disrupts the intestinal flora resulting in unwanted side effects. Naturopathic treatments often have fewer side effects and lower secondary infection risk than pharmaceutical interventions making them ideal for pediatric use. This case report describes the effective treatment of a pediatric clinical case of C. difficile using naturopathic and complementary alternative medicines (CAMs) including black seed oil (Nigella sativa), bentonite clay, and probiotics. A healthy two-year-old patient presented to a pediatrician with symptoms of, and subsequently confirmed, C. difficile after having been recently hospitalized and treated for a gluteal abscess and cellulitis using clindamycin, vancomycin, and piperacillin/tazobactam. Through a shared decision-making process, the patient’s mother and providers developed a treatment plan for the C. difficile infection (CDI), which included black seed oil, bentonite clay, and Lactobacillus probiotics. No C. difficile was detected via stool immunoassay after 4 days of combined CAM therapy. Our results underscore the need for additional research regarding the effectiveness of naturopathic CAMs including black seed oil, bentonite clay, and probiotics as alternatives to antibiotic treatment of CDI in children.